Rewriting subtraction using addition can be helpful to keep track of the subtraction symbol when distributing. Start by rewriting this expression using addition.

3(−4y−5)
= 3(
+
)

1 answer

To rewrite the expression \(3(-4y - 5)\) using addition, we can distribute the negative signs inside the parentheses.

Here's how you can rewrite it:

\[ 3(-4y - 5) = 3(-4y) + 3(-5) = 3(+(-4y)) + 3(+(-5)) \]

So, you can write:

\[ 3( -4y - 5) = 3( +(-4y) + +(-5) ) \]

In this form, it clearly shows the addition of the terms as you apply the distribution.